Ecological Functions of Agricultural Soil Bacteria and Microeukaryotes in Chitin Degradation: A Case Study - Wieczorek, Adam S.; Schmidt, Oliver; Chatzinotas, Antonis; von Bergen, Martin; Gorissen, Antonie; Kolb, Steffen (Frontiers in Microbiology, 2019)
Chitin provides a valuable carbon and nitrogen source for soil microorganisms and is a major component of particulate organic matter in agricultural soils. To date there is no information on interaction and interdependence in chitin-degrading soil microbiomes. Since microbial chitin degradation occurs under both oxic and anoxic conditions and both conditions occur simultaneously in soil, the comparison of the active microbiome members under both conditions can reveal key players for the overall degradation in aerated soil. A time-resolved 16S rRNA stable isotope probing experiment was conducted with soil material from the top soil layer of a wheat-covered field. [13CU]-chitin was largely mineralized within 20 days under oxic conditions. Cellvibrio, Massilia, and several Bacteriodetes families were identified as initially active chitin degraders. Subsequently, Planctomycetes and Verrucomicrobia were labeled by assimilation of 13C carbon either from [13CU]-chitin or from 13C-enriched components of primary chitin degraders. Bacterial predators (e.g., Bdellovibrio and Bacteriovorax) were labeled, too, and non-labeled microeukaryotic predators (Alveolata) increased their relative abundance towards the end of the experiment (70 days), indicating that chitin degraders were subject to predation. Trophic interactions differed substantially under anoxic and oxic conditions. Various fermentation types occurred along with iron respiration. While Acidobacteria and Chloroflexi were the first taxa to be labeled, although at a low 13C level, Firmicutes and uncultured Bacteroidetes were predominantly labeled at a much higher 13C level during the later stages, suggesting that the latter two bacterial taxa were mainly responsible for the degradation of chitin and also provided substrates for iron reducers. Eventually, our study revealed that (a) hitherto unrecognized Bacteria were involved in a chitin-degrading microbial food web of an agricultural soil, (b) trophic interactions were substantially shaped by the oxygen availability, and (c) detectable predation was restricted to oxic conditions. The gained insights into trophic interactions foster our understanding of microbial chitin degradation, which is in turn crucial for an understanding of soil carbon dynamics.